Spells for Coming Out. - Wedde, Ian (Auckland University Press, 2013)
A collection of poems by one of New Zealand's major poets, Spells for Coming Out exhibits a unity derived from mood and circumstance. Memories of Europe, regrets at the absence of 'friends, fugitives and lovers', dominate the opening section, and recur later when the physical scene before the poet is Mount Cargill and Otago Harbour. The feeling is lyrical, the structure informal, the clues are there to be followed into layers of resonance and meaning.